Cleanliness and diet - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
The Gambia?s champion sheep and ram breeders explain the secrets of how they have won the best ram competition at the annual Tobaski festival for the last twelve years.